Bio-glasses : an introduction - Jones, Julian R.; Clare, Alexis (Chichester, West Sussex : Wiley, 2012)
This new work is dedicated to glasses and their variants which can be used as biomaterials to repair diseased and damaged tissues. Bio-glasses are superior to other biomaterials in many applications, such as healing bone by signaling stem cells to become bone cells.
The unique nature of glass / Alexis G. Clare -- Melt derived bioactive glass / Matthew D. O'Donnell -- Sol-gel derived glasses for medicine / Julian R. Jones -- Phosphate glasses / Delia S. Brauer -- The structure of bioactive glasses and their surfaces / Alastair N. Cormack -- Bioactive borate glasses / Steven B. Jung -- Glass-ceramics / Wolfram H'land -- Bioactive glass- and glass-ceramic coatings / Enrica Vern -- Composites containing bioactive glass / Aldo R. Boccaccini and Qi-Zhi Chen -- Inorganic-organic sol-gel hybrids / Yuki Shirosaki [and others] -- Dental applications of glasses / Leena Hupa and Antti Yli-Urpo -- Bioactive glass as synthetic bone grafts and scaffolds for tissue engineering / Julian R. Jones -- Glasses for radiotherapy / Delbert E. Day.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Biomedical materials; Glass; Biocompatible Materials; Glass; Drug Delivery Systems; Regeneration; Tissue Scaffolds; MEDICAL -- Allied Health Services -- Medical Technology; MEDICAL -- Biotechnology; MEDICAL -- Family & General Practice; MEDICAL -- Lasers in Medicine; TECHNOLOGY & ENGINEERING -- Biomedical; Biomedical materials; Glass; Electronic books